Paradigm Development and Communication in Scientific Settings: A Contingency Analysis - Cheng, Joseph L. C. (Academy of Management Journal, 1984)
The article discusses research pertaining to the paradigm concept as a contingency factor in relation to scientific performance. Several premises provide the theoretical underpinnings for this stud...